Diving Deep into Arrhythmias: Unravelling the Impact of Underwater Environments on Premature Ventricular Complexes in Divers - Ranic, Ivan; Jiravsky, Otakar; Cesnakova Konecna, Alica; Jiravska Godula, Bogna; Pesova, Petra; Chovancik, Jan; Neuwirth, Radek; Sknouril, Libor; Pudil, Radek; Plasek, Jiri (Journal of clinical medicine, 2024)
This review examines the relationship between the physiological demands of diving and premature ventricular complexes (PVCs) in divers. In the general population, some individuals have a greater tendency to experience PVCs, often without awareness or a clear understanding of the triggering factors. With the increasing availability and popularity of both scuba and apnoea diving, more people, including those with a predisposition to PVCs, are engaging in these activities. The underwater environment, with its unique stressors, may increase the risk of arrhythmogenic events, particularly PVCs. Here, we review the prevalence, pathophysiology, and aggravating factors of PVCs in divers, emphasising the need for a comprehensive cardiovascular assessment. Evidence suggests a higher prevalence of PVCs in divers compared with the general population, influenced by factors such as age, dive depth, gas bubbles, cold water immersion, pre-existing cardiovascular diseases, and lifestyle factors. The change in environment during diving could potentially trigger an increased frequency of PVCs, especially in individuals with a pre-existing tendency. We discuss diagnostic strategies, management approaches, and preventive measures for divers with PVCs, noting that although guidelines for athletes can be adapted, individual assessment is crucial. Significant knowledge gaps are identified, highlighting the need for future research to develop evidence-based guidelines and understand the long-term significance of PVCs in divers. This work aims to evaluate potential contributing factors to PVCs in divers and identify individuals who may be at higher risk of experiencing major adverse cardiovascular events (MACEs). This work aims to improve diver safety by promoting collaboration between cardiologists and diving medicine specialists and by identifying key areas for future investigation in this field. This work aims to improve the safety and well-being of divers by understanding the cardiovascular challenges they face, including pressure changes, cold water immersion, and hypoxia. We seek to elucidate the relationship between these challenges and the occurrence of PVCs. By synthesising current evidence, identifying knowledge gaps, and proposing preliminary recommendations, we aim to encourage collaboration between cardiologists and diving medicine specialists to optimise the screening, management, and risk stratification of PVCs in the diving population.
Keywords: arrhythmias in divers; scuba diving; diving physiology; underwater medicine; premature ventricular complexes; apnoea diving